Variation of quality of life in patients with Obstructive Sleep Apnea Hypopnea Syndrome after treatment with mandibular advance device - Chávez-Gonzáles, César (2022)
Objective: To determine the variation of the Quality of Life in patients with mild to moderate Obstructive Sleep Apnea Hypopnea Syndrome, after treatment with the Mandibular Advancement Device at an altitude of 3259 masl. Methods: Prospective, quasi-experimental study. Subjects with respiratory disturbance index (RDI) between 5 and 30 / hour (measured with respiratory polygraphy), without previous treatments, with conditions for the use of MAD were included. The quality of life was assessed with the FOSQ (questionnaire of functional sleep results) before and after 45 days of treatment with MAD. Results: 26 completed the study (20 males). The mean (SD) of the age was 43 (9.6) years, BMI was 29 (8.6) kg / m2, and the RDI was 19 (7.6) / hour. After 45 day, significant changes were observed, with respect to the baseline values, in the FOSQ score (total calculation, general productivity, social outcome, activity level, vigilance and intimate relationships/sexual activity, p <0.001). The mean RDI decreased from 19 (7.6) to 7 (3.8) (p <0.001), the minimum desaturation of O2 increased from 77 (5.2) to 83 (3.9) (p <0.001), the T90 decreased from 73 (15.4) to 31 (16.6) (p <0.001) y Epworth's score decreased from 11.2 (4.6) to 6.4 (3.5) (p <0.001). Conclusions: In patients with mild-moderate OSA, treatment with MAD produces significant improvement in their quality of life, reduces the level of disease expressed in decreased RDI, improves oxygenation level and reduces daytime sleepiness expressed in decreased Epworth score.